Prevalence of Buruli ulcer in Akonolinga health district, Cameroon: results of a cross sectional survey. - Klaudia Porten; Karen Sailor; Eric Comte; Adelaide Njikap; Agnes Sobry; Francois Sihom; Abanda Meva'a; Sarah Eyangoh; Mark Myatt; Fabienne Nackers; Rebecca F Grais (PLoS Neglected Tropical Diseases, 2009)
BACKGROUND: Buruli ulcer (BU) is a chronic, indolent necrotizing disease of the skin and underlying tissues caused by Mycobacterium ulcerans, which may result in functional incapacity. In 2002, Médecins Sans Frontières (MSF) opened a BU programme in Akonolinga Hospital, Cameroon, offering antibiotic treatment, surgery and general medical care. Six hundred patients have been treated in the project to date. However, due to the nature of the disease and its stigmatization, determining the exact prevalence and burden of disease is difficult and current estimates may not reflect the magnitude of the problem. The objectives of this survey were to estimate the prevalence of BU in the health district of Akonolinga, describe the geographic extension of the highly endemic area within the health district, and determine the programme coverage and its geographical distribution. METHODOLOGY/PRINCIPAL FINDINGS: We conducted a cross-sectional population survey using centric systematic area sampling (CSAS). A 15x15 km grid (quadrats of 225 km(2)) was overlaid on a map of Akonolinga district with its position chosen to maximize the area covered by the survey. Quadrats were selected if more than 50% of the quadrat was inside of the health district. The chiefdom located closest to the centre of each quadrat was selected and Buruli cases were identified using an active case finding strategy (the sensitivity of the strategy was estimated by capture-recapture). WHO-case definitions were used for nodules, plaque, ulcer, oedema and sequelae. Out of a total population of 103,000 inhabitants, 26,679 were surveyed within the twenty quadrats. Sensitivity of the case finding strategy was estimated to be 84% (95%CI 54-97%). The overall prevalence was 0.47% (n = 105) for all cases including sequelae and 0.25% (n = 56) for active stages of the disease. Five quadrats had a high prevalence of >0.6% to 0.9%, 5 a prevalence >0.3% to 0.6% and 10 quadrats <0.3%. The quadrats with the high prevalence were situated along the rivers Nyong and Mfoumou. Overall coverage of the project was 18% (12-27%) for all cases and 16% (9-18%) for active cases, but was limited to the quadrats neighbouring Akonolinga Hospital. CONCLUSIONS/SIGNIFICANCE: Prevalence was highest in the area neighbouring the Nyong River. Coverage was limited to the area close to the hospital and efforts have to be made to increase access to care in the high prevalence areas. Use of the CSAS method was particularly useful for project planning and to identify priority areas of intervention. An added benefit of the method is that the survey procedure incorporated an awareness campaign, providing information about the disease and treatment to the population.